Efficient editing of an adenoviral vector genome with CRISPR/Cas9 - Qiang Li; Chen Z; Chen Z; Gong C-y; Shao Hong-w; Wang H; Yang J-x; Zhang W-f (Indian Journal of Microbiology, 2021)
Immunotherapy based on genetic modification of T cells has played an important role in the treatment of tumors and viral infections. Moreover, adenoviral vectors engineered with improved safety due to their inability to engineered with improved safety due to their inability to integrate into the host genome have been key in the clinical application of T cells therapy. However, the commonly used adenoviral vector Ad5 exhibits low efficiency of infection of human T cells and the details of the intracellular trafficking pathway of adenoviral vectors in human primary T cells remains unclear. Resolution of these issues will depend on successful modification of the adenoviral vector. To this end, here we describe the successful establishment of a simple and efficient method for editing adenoviral vectors in vitro using the CRISPR-Cas9 gene editing system to target the adinoviral fiber gene.
Source Year: 2021
Keywords: Adenoviral vector; CRISPR-Cas9; T-cell therapy